Pengaruh Konsentrasi Natrium Metabisulfit Dan Lama Perendaman Terhadap Mutu Keripik Kentang - Tampubolon, Sanggam Dera Rosa (Jurnal Riset Teknologi Pangan dan Hasil Pertanian (RETIPA), 2020)
This study aims to determine the effect of the concentration and duration of soaking of Sodium Metabisulfite on the quality of potato chips. The study was conducted with a factorial Complete Randomized Design (CRD), which consisted of two treatment factors. The first factor concentration of Sodium Metabisulfite with the code N, consists of 4 levels, namely: N0 = 0% (control), N1 = 1%, N2 = 2% and N3 = 3%. The second factor of the immersion time with the code L, consists of 4 levels, namely: L0 = 0 minutes (control), L1 = 30 minutes, L2 = 60 minutes and L3 = 90 minutes. Data analysis was performed with LSR (Least Significant Ranges) test.The results showed that the concentration of Sodium Metabisulfite had a significantly different effect (P <0.01) on water content, ash content, protein content, and fat content. The higher the concentration of Sodium Metabisulfite, the fat content decreases, while the water content, ash content, and protein content increase. Soaking time gave a very significant effect (P <0.01) on the water content, ash content, protein content, and fat content. The longer the immersion time, the higher water content, and fat content while protein content, fat content content decrease. The interaction between Sodium Metabisulfite Concentration and soaking time had a very significant effect (P <0.01) on ash content.